Deconvoluting effects of vine and soil properties on grape berry composition - Zerihun, Ayalsew; Mcclymont, L.; Lanyon, D.; Goodwin, I.; Gibberd, M. (John Wiley and Sons Ltd, 2015)
BACKGROUND: Grape berry composition is influenced by several factors including grapevine and soil properties and their interactions. Understanding how these factors interact to determine berry composition is integral to producing berries with desired composition. Here we used extensive spatio-temporal data to identify significant vine and soil features that influence Shiraz berry composition. RESULTS: The concentrations of berry flavonoids (anthocyanins, tannin and total phenolics), total soluble solids and pH were typically negatively associated with canopy, crop and berry size factors whereas titratable acidity was positively associated. The strengths of the associations, however, were generally greater with the crop and berry size factors than with the canopy size factor. The analyses also resolved separate influences of berry and crop size on berry composition. Soil properties had significant influences on berry composition; however, when influences of soil factors on vine-attributes were accounted for, the apparent effects of soil factors on berry composition were largely non-existent. CONCLUSION: At each site, variations in berry composition were more strongly associated with crop and berry size than with canopy size factors. Apparent influences of soil properties on berry composition are indirect, being mediated via their effects on vine attributes (canopy, crop and berry sizes).